Tissue Extract and the Contact Reaction in Blood Coagulation - Biggs, Rosemary; Nossel, H. L (Thrombosis and Haemostasis, 1961)
1. The addition of dilute brain extract to normal silicone collected plasma or to celite exhausted normal plasma produces an acceleration of thrombin formation similar to that of kaolin on normal plasma.2. When dilute brain extract is added to PTA or Hageman deficient plasma samples, the concentration of brain required to simulate the kaolin activated normal contact mechanism is similar to that required for normal plasma. When very dilute brain extract is used the reaction of the Hageman deficient sample is defective.3. When added to factor VIII or factor IX deficient plasma samples about ten times as much brain extract is required to produce the type of thrombin generation curve typically found on the addition of kaolin to silicone collected normal plasma.4. It is suggested that in normal haemostasis the contact phase may be initiated, in part at least, by weak tissue extracts liberated at a site of injury.